PENGARUH DIVIDEN, KEBIJAKAN UTANG DAN KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN INDEKS LQ45 DI BURSA EFEK INDONESIA TAHUN 2019-2023 - Setyawati, Dias Fitri; Cahyani , Yenni (Publika Citra Media, 2024)
This study aims to analyze the effect of Dividends, Debt Policy, and Financial Performance on Stock Prices. This study was conducted by analyzing the financial statements of LQ45 Index companies listed on the Indonesia Stock Exchange during the 2019-2023 period. This study uses secondary data in the form of annual financial reports from the Indonesia Stock Exchange. The type of research used is quantitative with an associative method. The sampling technique in this study used the purposive sampling method, obtained as many as 12 companies with a time span of 5 years, so that the data processed was 60 data samples. The data analysis technique in this study used the panel data regression analysis method and the data analysis tool in this study used the Eviews version 13 software program. The results of this study indicate that simultaneously the Dividend, Debt Policy, and Financial Performance variables together have a significant effect on Stock Prices. And the partial results of the study indicate that the Dividend variable has a significant negative effect on Stock Prices, the Debt Policy variable does not have a significant effect on stock prices, and the Financial Performance variable has a significant positive effect on Stock Prices.